154: Objectively Measured Physical Activity of Infants, Toddlers, and Preschool-Aged Children Using Accelerometry. Issue 6 (1st June 2014) - Heale, L; Borkhoff, CM; Maguire, JL; Parkin, PC; Birken, CS
Abstract: BACKGROUND: Increased physical activity (PA) in early childhood is associated with improved measures of body composition, motor skill, cognitive development and cardiometabolic health indicators. There are very few studies describing objectively measures of PA in very young children using accelerometry. OBJECTIVES: To describe the objectively measured PA levels of infants, toddlers, and preschoolers and assess their compliance with the recently published Canadian physical activity guidelines for this age group. DESIGN/METHODS: Children aged four months to five years (n=54) recruited through a primary care practice based research network in Canada wore Actical accelerometers for seven consecutive days. Data were collected in two-second epochs and participants with four or more valid days were included in the analysis. Moderate to vigorous physical activity (MVPA), light physical activity (LPA), and sedentary activity (SA) were calculated using published cut-points for preschoolers. The mean minutes per day (min/d) of MVPA, LPA, and SA were reported by age group (<18 months, and ≥18 months) and sex. RESULTS: Children 18 months of age and older (n=31) accumulated a mean (95% CI) of 35 min/day (26 to 45 min/day) of MVPA, 208 min/day (194 to 221 min/day) of LPA, and 390 min/day (370 to 410 min/day) of SA. Children under 18 months (n=23) accumulated a mean (95% CI) of 4 min/day (3 to 6 min/day) of MVPA, 94 min/day (71 to 116 min/day) of LPA and 452 min/day (426 to 477 min/day) of SA. Ninety-two percent of children 18 months to four years of age (n=26) and 17 percent of children under 18 months met the Canadian PA guidelines for children aged 0 to 4 of 180 min of total daily PA. There were no significant differences in boys compared to girls in MVPA: 20 (9 to 31) vs. 24 (14 to 33); P=0.60, LPA: 152 (120 to 183) vs. 165 (139 to 191); P=0.50, or SA: 414 (391 to 437) vs. 418 (391 to 445); P=0.85. CONCLUSIONS: Children over 18 months seem to be meeting Canadian PA guidelines. While children under 18 months appeared relatively inactive, further research is necessary to validate accelerometer-based physical activity measurement and cut-points in this age group.